C-reactive protein to serum calcium ratio as a novel biomarker for predicting severity in acute pancreatitis: a retrospective cross-sectional study - Xinqi Chen; Yisen Huang; Qiaoli Xu; Bifeng Zhang; Yubin Wang; Meixue Huang (Frontiers in Medicine)
BackgroundAcute pancreatitis (AP) is a prevalent gastrointestinal emergency with a wide spectrum of clinical outcomes, varying from mild cases to severe forms. The early identification of high-risk patients is essential for improving prognosis. However, the predictive and prognostic potential of the C-reactive protein to serum calcium ratio (CCR) in AP has not been investigated. This study aims to explore the association between CCR and disease severity in patients with AP.MethodsThis retrospective cross-sectional study included 476 AP patients. The CCR was calculated from C-reactive protein and serum calcium levels within the first 24 h of admission. Multivariable logistic regression models were used to evaluate the relationship between CCR and AP severity, with restricted cubic spline analysis and receiver operating characteristic (ROC) analysis to assess dose–response and predictive performance, respectively.ResultsOf the 476 patients, 176 (37%) had mild acute pancreatitis (MAP) and 300 (63%) had moderate to severe AP. The CCR distribution had a median value of 17.5, with an interquartile range (IQR) of 3.0 to 60.2. Each unit increase in CCR was associated with a 7% increase in the risk of developing moderate to severe AP (OR: 1.07; 95% CI: 1.06–1.09). In fully adjusted models, this association remained statistically significant. The area under the curve (AUC) for CCR in predicting moderate to severe AP was 86.9%, with a sensitivity of 73.7% and specificity of 89.2%.ConclusionThe CCR measured within the first 24 h of admission shows promise as a valuable biomarker for predicting the severity of AP. However, further multicenter prospective cohort studies are needed to confirm its clinical utility and investigate its role in improving treatment strategies and patient management.